The pathophysiology of heart failure - Ashrafian, H; Rosen, S (2002)
With increased identification of ischaemic heart disease and hypertension, heart failure - the inability of the myocardium to maintain adequate tissue perfusion, is a major and increasingly important contributor to population morbidity and mortality. Over the past 50 years, physicians have refined their understanding of heart failure, changing the focus of disease pathogenesis from, the paradigm of primary cardiac dyscontractility, to that of systemic endothelial activation and up-regulation of the cardio-renal axis, culminating in the neurohormonal hypothesis. By initially detailing advances made in the molecular biology of cardiomyopathies, we describe the principal determinants of primary muscle disease, and examine them as pure models of systemic neurohormonal activation. By further incorporating myocardial energetics, systemic inflammatory responses, mechanisms ofapoptosis and cell signalling into the neurohormonal hypothesis we propose a unified schema of how diverse insults acting on the myocardium converge to a single systemic final common path resulting in the vicious cycle of progressive heart failure. This model provides a rationale to explain the efficacy of existing successful treatments and identify novel treatment modalities. Furthermore it provides a molecular explanation for the signs of symptoms of both systolic and diastolic dysfunction of both ventricles.